Steroid anabolic and catabolic hormones in highly and recreationally trained female athletes across the menstrual cycle - Collomp, K.; Castanier, C.; Teulier, C.; Olivier, A.; Blanchard, L.; Bonnigal, J.; Duron, E.; Favory, E.; Zimmermann, M.; Amiot, V.; Carité, V.; Lefebvre, M.; et al. (Physiological Reports, 2025)
Sex hormone fluctuations across the normal menstrual cycle (NMC) may affect women's performance and health, but literature is sparse on the estradiol (E2) impact on anabolic and catabolic hormones and well-being in female athletes. We therefore measured in 21 NMC anaerobically trained female athletes: 12 highly (HT) and nine recreationally (RT) during late luteal/early follicular (Low E2) and late follicular/peri-ovulatory (High E2) phases: DHEAS, DHEA, androstenedione (A4), testosterone (T), sex hormone-binding globulin (SHBG), cortisol, free androgen index (FAI = T/SHBG), and their relative ratios. Body composition and well-being, assessed by positive and negative affects (PANAS), were determined in parallel. In High versus Low E2, subjects showed a significant percentage increase in T, A4 (p < 0.001) and FAI (p < 0.05), with high A4/T correlation (r = 0.78), without any change in the other parameters. While no group difference was detected in hormone concentrations, HT versus RT subjects presented higher muscle mass and positive affects and lower FAI (p < 0.05). In conclusion, T and A4 were modulated across NMC, probably resulting from a variable ovarian contribution, but without inducing any change in the anabolic/catabolic balance, regardless of the physical training level. However, high anaerobic training may enhance T sensitivity in view of the FAI, body composition and well-being outcomes.